2018
DOI: 10.1001/jamainternmed.2017.8049
|View full text |Cite
|
Sign up to set email alerts
|

Web Platform vs In-Person Genetic Counselor for Return of Carrier Results From Exome Sequencing

Abstract: IMPORTANCE A critical bottleneck in clinical genomics is the mismatch between large volumes of results and the availability of knowledgeable professionals to return them. OBJECTIVE To test whether a web-based platform is noninferior to a genetic counselor for educating patients about their carrier results from exome sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 37 publications
1
58
1
Order By: Relevance
“…Other studies similarly suggest that given cost constraints, workforce shortages and the complexity of genomic information, innovative approaches, like web‐based education and results disclosure, could be an acceptable alternative to the two‐visit genetic counseling model (Biesecker et al, ; Green, Biesecker, McInerney, Mauger, & Fost, ; Green et al, , ; Roberts et al, ; Sweet et al, ). Two studies that used an on‐line educational tool as an adjunct in advance of pretest counseling, reported the intervention was an effective way to learn about the issues, participants valued it for being self‐paced, private and an efficient use of their time (Green et al, ), and was associated with increased knowledge about heredity breast cancer and genetic testing, without increasing anxiety (Green et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies similarly suggest that given cost constraints, workforce shortages and the complexity of genomic information, innovative approaches, like web‐based education and results disclosure, could be an acceptable alternative to the two‐visit genetic counseling model (Biesecker et al, ; Green, Biesecker, McInerney, Mauger, & Fost, ; Green et al, , ; Roberts et al, ; Sweet et al, ). Two studies that used an on‐line educational tool as an adjunct in advance of pretest counseling, reported the intervention was an effective way to learn about the issues, participants valued it for being self‐paced, private and an efficient use of their time (Green et al, ), and was associated with increased knowledge about heredity breast cancer and genetic testing, without increasing anxiety (Green et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies that used an on‐line educational tool as an adjunct in advance of pretest counseling, reported the intervention was an effective way to learn about the issues, participants valued it for being self‐paced, private and an efficient use of their time (Green et al, ), and was associated with increased knowledge about heredity breast cancer and genetic testing, without increasing anxiety (Green et al, ). A recent randomized study that compared education and disclosure of carrier results by a web‐platform versus a genetic counselor, reported that the web‐based arm was noninferior for knowledge, distress and decisional regret (Biesecker et al, ). Of note, and as acknowledged by the authors, this was a highly select population who were undergoing relatively low risk testing (e.g., carrier testing with less direct implication for health care).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many CSER translational research projects disclosed carrier results as a secondary result. Several projects have published outcomes that include carrier testing (Biesecker et al., ; Cirino et al., ; Lewis et al., ; Parsons et al., ; Vassy et al., ; Wynn et al., ). The Consortium's Actionability/Return of Results Working Group sought to understand the variability in CSER approaches to identifying and disclosing carrier results, including (1) selection of genes and variants; (2) choices given to research participants regarding which results to disclose; (3) results communication approaches; and (4) project outcomes, including the proportion of individuals with carrier results and which genetic variants are commonly identified.…”
Section: Introductionmentioning
confidence: 99%